Effects of antidepressant therapy on neural components of verbal working memory in depression. (September 2017) - Sankar, Anjali; Adams, Tracey M; Costafreda, Sergi G; Marangell, Lauren B; Fu, Cynthia HY
Impairments in verbal working memory are evident in major depression. Verbal working memory is comprised of the components of encoding, maintenance and retrieval. Whether the neural impairments are expressed in specific components, and how pharmacological therapy could modify the neural correlates are not well understood. We investigated the neural correlates of verbal working memory components in depression using the Sternberg task in a longitudinal magnetic resonance imaging study. Serial scans were acquired in 23 patients (mean age 39.8 years) during an acute depressive episode and following 12 weeks of pharmacological therapy with duloxetine and in 22 matched healthy controls (mean age 39.1 years) at the same time points. A significant group by time interaction was evident during the long maintenance phase, extending from the left middle frontal to the middle temporal and caudate regions, in which there was reduced activation in healthy participants at the follow - up scan but there were no changes in patients. Persistent neural engagement during the maintenance phase following treatment was revealed in major depression. The findings emphasize that impairments in verbal working memory may be initiated in the maintenance phase in major depression in order to sustain performance. Further research with larger sample size and using randomized, placebo-controlled double-blind studies are required to confirm our results.